Docência universitária: o professor de Direito formado em Direito - Silva, Naísa Afonso da (2011)
This research deals with academic teaching , above with Law professor. Its main aim is to understand what Law college professors with an academic background in law think of their education and pedagogical practices. It seeks to indicate the interactions between them and with the organization of their teaching work . Methodological procedures have included openand closed-question questionnaire applied following quantitative and qualitative approach. Data were analyzed through Microsoft Office Excel 2007 version. Research subjects have included forty-four professors from three academic institutions. Results reveal that academic law teaching practice is still conservative and prioritize content transmission; and that students education focuses on professional work and on the Brazilian lawyers professional association exams. Although it has made clear that the absence of pedagogical training interferes directly and negatively with these professors teaching, 90,9 per cent of them did not refer to the importance of the pedagogical training to their work. Therefore, Law college teachers are supposed to have pedagogical training, since it can enhance learning quality